SYSTEMATIC STUDY OF PUBLIC ADMINISTRATION OF THE NATIONAL ECONOMY - LYSYUK, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2022)
With the development of the democracy and civil society there is an evolutionary development of public administration, the transition from the traditional vision of public administration as organizing and regulating the influence of the state on public life in order to organize, maintain or transform, based on its power, to its new models, namely: New Public Management ("new public management", "new public administration"), the theory of socio-political networks (Social-Political Networks) and the concepts of Governance and New Governance, which were a response to the crisis in government based on the principles of bureaucracy, hierarchical organization and centralization. New Public Management involves privatization and the elimination of the excessive regulation, removing the single structure outside or autonomy of the individual administrative units, introducing elements of competition in administrative activities, as well as borrowing management methods from the private economy to the public administration sector. The concept of socio-political networks (Social-Political Networks) defines approaches to improving the management of public affairs based on the formation of a set of integrated state and non-state entities in various spheres of public life, their interaction based on common interest, resource dependence, horizontal formal and informal relations. According to the concept of Governance, the emphasis is on creating a transparent and democratic mechanism for the formation and implementation of management decisions. The essence of the concept of governance "Good Governance" is to involve all social institutions in the management: the state, the private sector and civil society. Based on the systematic study of public administration, we argue that public administration is a form of practical implementation of the activities of all branches of government (legislative, executive, judicial) to develop and implement regulatory, organizing and coordinating influences on all spheres of society, including the national economy.